Study the Teacher Empowerment in reference to Administrative Behaviour of School Heads working in Rural and Urban Schools - Pathak, Priya; Goswami, Dr.Vandana (IJRDO-Journal of Applied Science, 2015)
With the liberalization and the globalization of the Indian economy, the rapid changes witnessed in the scientific and technological world, and it is realized that the emerging Indian society can achieve all round development with the help of the teachers who act as a powerful agency in transmitting its cherished values. So here an empowered teacher is the necessity of the society. The objective was to study the Teacher Empowerment in reference to Administrative Behaviour of School Heads working in Rural and Urban schools. The sample of this study comprises 48 Heads, 405 teachers from different senior secondary (10+2) Rural and Urban schools of Agra division (U. P.). For measuring Administrative Behaviour of School Heads, Administrative Behaviour scale developed by Dr. Haseen Taj in 1998 was used and Teacher Empowerment scale was prepared by the researcher. The finding of this study states that differences found in Teacher Empowerment of Rural and Urban school teachers in reference to their Administrative Behaviour of School Heads.